Comparison of outcome in between single tract and multiple tract percutaneous nephrolithotomy in the management of staghorn calculus (Bangladesh Journal of Urology, 2025)
Background: Staghorn calculi are branched and generally infected stones that occupy a large portion of the collecting system. Failure to eliminate complex staghorn stones presumably destroys the kidney and causes sepsis as well as complete loss of function. Percutaneous nephrolithotomy (PCNL) is currently the accepted firstline treatment option for staghorn calculi with various auxiliary procedures.Objective: To assess the efficacy and the safety of single versus multiple tract PCNL in the management of staghorn stones.Materials and Methods: This study was carried out in the department of Urology, National Institute of Kidney Diseases and Urology, Dhaka from November 2020 to November 2021. Sixty patients were selected by purposive sampling technique and allocated into two groups as single tract PNCL (Group-A) and multiple tract PCNL (Group-B). Both groups were compared in terms of efficacy and safety outcomes: Stone free rate, Duration of operation, Postoperative hemoglobin drop, blood transfusion, complications, Hospital stay and renal function.Results: Mean age was 41±13.81 years in Group-A and 39.63±11.16 years in Group-B. Mean stone size was 6.21±2.68 cm in Group-A and 6.62±2.65 cm in Group-B respectively with no statistically significant difference (P=0.555). Mean operation time of Group-A was 74.53±5.16 minutes and of Group-B was 82.03±3.86 minutes with no significant difference. Mean hemoglobin drop in Group-A was 1.99±0.49 g/dl and 2.60±0.13 g/dl in Group-B with statistically significant difference (P=0.001). Percentage of blood transfusion was 13.3% in Group-A and 30% in Group-B (P=0.117). An overall stone clearance rate was 73.3% in Group-A and 83.3% in Group-B (P=0.559). In both group, there was no statistical difference in post operative hospital stay (P= 0.325), post operative serum creatinine (P=0.72), post operative complications (P=0.317) and post operative follow up after one month (P=0.488).Conclusion: This study showed that STPCNL is an effective method for treating complex caliceal calculi or staghorn stones. Compared with MTPCNL, STPCNL not only yields similarly high SFRs but also is associated with many advantages, less blood loss, fewer blood transfusions, and less complications.Bangladesh J. Urol. 2024; 27(2): 95-100